The Contribution of Arabic Learning To Improve Religious Materials for Students - Amrina Amrina; Iswantir M Iswantir M; Adam Mudinillah; Ahmad Firdaus bin Mohd Noor (Ijaz Arabi Journal of Arabic Learning, 2022)
This study aims to determine how big the contribution of Arabic courses to the improvement of religious material for students of the Tarbiyah Faculty of Teacher Training and Education, Batusangkar State Islamic Institute. This study uses survey methods and data collection techniques through a google form, which can be seen through student learning outcomes. The research sample was students of the Tarbiyah Teacher Training Institute at the State Islamic Institute of Batusangkar who had studied Arabic. From the results or data obtained, the researcher concludes that Arabic language courses contribute to improving religious material for students of the Tarbiyah Faculty of Teacher Training and Education, Batusangkar State Islamic Institute. A positive indicator of learning Arabic in religious subjects is that students can read and understand Arabic texts even though they are not majoring in Arabic. It is evident in the courses from several departments at the Batusangkar State Islamic Institute, namely the Department of Islamic Religious Education (PAI) in the Ulumul Quran and Ulumul Hadith courses, the Department of Madrasah Ibtidaiyah Teacher Education (PGMI) in the Qur'an course. And Hadith and the Department of Early Childhood Islamic Education (PIAUD) in Tarbawi Hadith and Tarbawi Tafsir courses. A positive indicator of learning Arabic in religious subjects is that students can read and understand Arabic texts even though they are not majoring in Arabic. Quran and Ulumul Hadith, majoring in Madrasah Ibtidaiyah Teacher Education (PGMI) in the Al-Qur'an Hadith course and majoring in Early Childhood Islamic Education (PIAUD) in Tarbawi Hadith and Tafsir Tarbawi courses.